Developing Differentiated Learning Videos to Improve Early Childhood Science Skills - isti hidayati; Dadan Suryana; Nurhafizah; Yaswinda (Universitas Ahmad Dahlan, 2026)
Science learning in early childhood education is essential for developing curiosity, observation, and early reasoning skills. However, science instruction in many kindergarten settings still relies on conventional media that do not adequately address children’s diverse learning needs. This study aimed to develop differentiated learning videos on the topic of plants to improve the science skills of early childhood among private kindergarten students in Batam City. Using a research and development approach, the study followed the ADDIE model: analysis, design, development, implementation, and evaluation. Participants were children aged 5–6 years involved in small- and medium-group trials. Data were collected through expert validation sheets, teacher practicality questionnaires, and observations of children’s science skills. The results showed that the video was highly valid, practical, and effective, with validation scores of 86% and 98%, a practicality score of 95%, and effectiveness scores ranging from 87% to 89%. The findings suggest that differentiated plant-learning videos can effectively enhance young children’s science skills.